The Efektifitas Model Pembelajaran Flipped Classroom Terhadap Pemahaman Konsep Mata Kuliah Ekonomi Pendidikan Pada Mahasiswa Pendidikan Ekonomi FKIP Universitas Jambi (Universitas Negeri Semarang, 2023)
The focus of the objectives of this study were to 1) determine the effectiveness of conventional learning models on understanding the concepts of educational economics courses; 2) determine the effectiveness of the Flipped Classroom learning model for understanding the concepts of educational economics courses; 3) find out the comparison of the effectiveness of learning using conventional learning models and Flipped Classroom towards understanding the concepts of educational economics courses in Economics Education students at FKIP Jambi University. The researcher determined that the control class was class R002 with 37 students and the experimental class was class R001 with 39 students. The data analysis technique used is descriptive analysis and Ancova test analysis. Prior to the Ancova test stage, the classical assumption test was carried out first, namely the normality test, uniform homogeneity and linearity. The results of this study are 1) the use of conventional learning models (lectures) is not effective for students' understanding of the learning concepts in educational economics courses, because the average scores obtained by students do not experience a significant increase; 2) the use of the Flipped Classroom learning model is quite effective for students' understanding of the concept of learning in educational economics courses, because the average scores obtained by students have increased quite significantly; and 3) the results of the Tests of Between-Subjects Effects obtained a significance level in the